Association of Social Adversity with Comorbid Diabetes and Depression Symptoms in the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study: A Syndemic Framework. Issue 11 (5th April 2019) - McCurley, Jessica L; Gutierrez, Angela P; Bravin, Julia I; Schneiderman, Neil; Reina, Samantha A; Khambaty, Tasneem; Castañeda, Sheila F; Smoller, Sylvia; Daviglus, Martha L; O'Brien, Matthew J; Carnethon, Mercedes R; Isasi, Carmen R; et al.
Abstract: Background: U.S. Hispanics/Latinos experience high lifetime risk for Type 2 diabetes and concurrent psychological depression. This comorbidity is associated with poorer self-management, worse disease outcomes, and higher mortality. Syndemic theory is a novel social epidemiological framework that emphasizes the role of economic and social adversity in promoting disease comorbidity and health disparities. Purpose: Informed by the syndemic framework, this study explored associations of socioeconomic and psychosocial adversity (low income/education, trauma history, adverse childhood experiences, ethnic discrimination, neighborhood problems [e.g., violence]) with comorbidity of diabetes and depression symptoms in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) and Sociocultural Ancillary Study. Methods: Participants were 5, 247 Latino adults, aged 18–74, enrolled in four U.S. cities from 2008 to 2011. Participants completed a baseline physical exam and measures of depression symptoms and psychosocial adversity. Multinomial logistic regression analyses were conducted to examine associations of adversity variables with comorbid diabetes and high depression symptoms. Results: Household income below $30, 000/year was associated with higher odds of diabetes/depression comorbidity (odds ratio [OR] = 4.61; 95% confidence interval [CI]: 2.89, 7.33) compared to having neither condition, as was each standard deviation increase in adverse childhood experiences (OR = 1.41; 95% CI: 1.16, 1.71), ethnic discrimination (OR = 1.23; 95% CI: 1.01, 1.50), and neighborhood problems (OR = 1.53; 95% CI: 1.30, 1.80). Conclusion: Low household income, adverse childhood experiences, ethnic discrimination, and neighborhood problems are related to comorbid diabetes and depression in U.S. Latinos. Future studies should explore these relationships longitudinally. Abstract : Low household income is associated with comorbidity of diabetes and high depression symptoms in U.S. Latinos. Adverse childhood experiences, discrimination, and neighborhood problems are associated with comorbidity compared to having neither condition.